PENERAPAN STRATEGI RECIPROCAL TEACHING UNTUK MENINGKATKAN HASIL BELAJAR MATA PELAJARAN BIOLOGI PADA SISWA KELAS XI IPA 1 MAN BANYUWANGI SEMESTER GANJIL TAHUN PELAJARAN 2020 – 2021 - Totok Hari Prasetiyo (Nusantara Hasana Berdikari, 2021)
The problem at MAN Banyuwangi is the low classical completeness of students caused by the lack of active students in the learning process so that learning outcomes on daily test 1 are low, namely 57.5% of 40 students. The formulation of the problem that the researchers took was whether learning history using reciprocal teaching strategies could improve learning outcomes for biology subjects in class XI IPA 1 MAN Banyuwangi odd semesters for the academic year 2020 – 2021. The scope of the research was MAN Banyuwangi class XI IPA 1 in odd semesters. in biology lessons. Reciprocal teaching is a constructivist approach that is based on the principles of making / asking questions where metacognitive skills are taught through direct teaching and modeling by teachers to improve student achievement. This classroom action research was carried out in two cycles, each cycle consisting of 2 meetings and one test. The KKM for biology subjects is 65 with a classical mastery target of 85%. After going through several CAR processes consisting of planning, action, observation and reflection, it can be seen that there is an increase in student learning outcomes from before the study whose classical completeness was 57.5% to 77.5% in cycle one and 87.5% in cycle II. so that this research is considered successful. There is also an increase in the class average of students' test results. Before the action, the average class of students reached 67.23. In the first cycle test, the average student was 72.75 and in the second cycle it increased to 79.25